2010
DOI: 10.1103/physreva.82.042332
|View full text |Cite
|
Sign up to set email alerts
|

Unruh effect in quantum information beyond the single-mode approximation

Abstract: We address the validity of the single-mode approximation that is commonly invoked in the analysis of entanglement in non-inertial frames and in other relativistic quantum information scenarios. We show that the single-mode approximation is not valid for arbitrary states, finding corrections to previous studies beyond such approximation in the bosonic and fermionic cases. We also exhibit a class of wave packets for which the single-mode approximation is justified subject to the peaking constraints set by an app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
448
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(462 citation statements)
references
References 40 publications
9
448
5
Order By: Relevance
“…Now, it is well known that for different observers in uniform relative motion the total amount of entanglement is the same in all inertial frames, although they don't agree on the amount of entanglement among various degree of freedom of the system. Also, more recently, quantum entanglement has been studied in relativistic non-inertial frames [9][10][11][12][13][14][15][16][17]. Alsing and Milburn extended the argument to a situation where one observer is uniformly accelerated [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, it is well known that for different observers in uniform relative motion the total amount of entanglement is the same in all inertial frames, although they don't agree on the amount of entanglement among various degree of freedom of the system. Also, more recently, quantum entanglement has been studied in relativistic non-inertial frames [9][10][11][12][13][14][15][16][17]. Alsing and Milburn extended the argument to a situation where one observer is uniformly accelerated [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that as a universality principle going beyond this approximation does not modify the way in which Unruh decoherence affects fermionic and bosonic entanglements. Unruh effect is independent of the number of field modes considered in the problem and statistics is the ruler of this process [16]. In tripartite discrete systems, two classes of genuine tripartite entanglement have been discovered, namely, the Greenberger-Horne-Zielinger (GHZ) class [22,23] and the W class [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…There occurred an entanglement degradation in such a state by the accelerated motion, which was commonly attributed to the thermalization due to the Unruh effect. Whereas for bosonic modes the entanglement vanished in the infinite acceleration limit [216] there still remained a non-zero residual entanglement in case of (anti-) fermionic modes [217]. So we asked ourself if this residual entanglement could be used for quantum information tasks.…”
Section: B Bell Inequalities In Particle Physicsmentioning
confidence: 99%
“…In beyond single mode approximation, an accelerated detector can detect a mode in both Rindler wedges I and II, therefore there are different right and left components for the single-particle state denoted as Alice [26],…”
Section: Superdense Coding In Beyond Single-mode Approximationmentioning
confidence: 99%